Exploring the Luxury Train Experience: A Case Study of the TranzAlpine Train - Patel, Khushbu Satish (Auckland University of Technology, 2024)
This dissertation aims to explore the key aspects that define a luxury train experience and assess the opportunities and risks of enhancing its appeal to luxury tourists. The research described here was rooted in a qualitative methodology, within an interpretive paradigm to analyse traveller reviews of 10 luxury trains worldwide from TripAdvisor, along with data from the TranzAlpine’s website. Through thematic analysis, the research identified eight main themes that define the luxury train experience: Memories, Service, Food and beverages, Cabin, Excursions, Booking, Onboard amenities, and Travel assurance. The study conducts an opportunity and risk analysis for incorporating these aspects into the TranzAlpine train service, aiming to transform it into a luxury tourism product. The findings suggest significant opportunities for the TranzAlpine to differentiate itself and attract luxury tourists by enhancing service quality, offering exclusive experiences, ensuring passenger comfort and satisfaction. However, risks such as the need for substantial investment, maintaining high service standards, and managing operational complexities must be carefully navigated. This dissertation contributes to the literature on luxury train tourism and offers theoretical and practical insights for industry practitioners. In providing a detailed analysis of luxury train travel and its application to the TranzAlpine, the study proposes eight recommendations that could redefine the service, turning it from a scenic journey into a luxurious and memorable travel experience.